The Belt and Road Initiative: Exploring Beijing's Motivations and Challenges for its New Silk Road. Issue 2 (4th March 2018) - Clarke, Michael
Abstract: This article argues that Beijing's ambitious 'Belt and Road Initiative' (BRI) is driven by the convergence of Innenpolitik and Aussenpolitik motivations including a desire: to counterbalance perceived American predominance; to ensure economic growth to underpin the CCP's legitimacy; and to present China as a viable alternate global leader to the United States. Due to challenges posed by Xinjiang and China's geopolitically 'hybridity', the most likely effect of the BRI will be the division of the Indo-Pacific into a sphere of Chinese predominance in its Eurasian continental setting and the maintenance of American predominance in its maritime setting.